Faith and freedom: The Qur’anic notion of freedom of religion vs. the act of changing religion and thoughts on the implications for Malaysia - Ismail, Siti Zubaidah; Awang Mat, Muhamad Zahiri (MDPI AG, 2016)
The issue of freedom of religion has always been situated at the intersection between human rights, personal freedom of choice, religious belief and apostasy. While freedom supporters argue that one is free to choose his or her religion, including changing religion, the Qur’an has made it clear that Islam allows changing of religion so long as it is from any religion to Islam and not from Islam to another religion. Apostatizing from Islam is one of the gravest enormities cautioned with eternal punishment. In interpreting the meaning of freedom of religion and restricting it from the “freedom” to change religion, Muslim scholars have been careful to draw a line distinguishing between the two. This article examines the different interpretations given by scholars on the issue of freedom of religion according to the Qur’an. By using historical and thematic analysis, the writers evaluate the mufassirins’ (scholars of exegesis) views on the related Qur’anic verses. Interpretations of the classical Islamic legal sources are also examined to identify their opinions on the consequences of leaving Islam, followed by contemporary opinions. The objective is to show the development and changes, if any, in the approaches taken regarding the limitations of freedom of religion. This will enlighten the ways to handle the issue of apostasy, as it is seen as a highly divisive and controversial issue, and to highlight an ideal approach for Malaysia.